SISTEM PENGAWASAN INTERNAL PEMERINTAH DAERAH KABUPATEN TANA TIDUNG DALAM PERSPEKTIF PRINSIP GOOD GOVERNANCE - Dimas Aditya (JURNAL AKTA YUDISIA, 2026)
This article analyzes the internal supervision system of the Tana Tidung Regency Government from the perspective of good governance principles. The discussion focuses on local government policy in implementing good governance within an integrated internal supervision system and the application of good governance principles in that system. This research uses normative juridical research with statutory and conceptual approaches. The findings show that internal supervision is an important instrument to ensure transparency, accountability, legal certainty, prevention of abuse of authority, and improvement of public services. Nevertheless, the implementation of integrated supervision still faces challenges, particularly the need for updated local regulations, stronger Government Internal Supervisory Apparatus, better coordination, technology-based monitoring, and integration between supervision results and regional financial management. Therefore, modernization of the supervision system and strengthening of institutional capacity are necessary to support clean, accountable, and responsive regional governance.